Research progress in fructose induced hyperuricemia and renal injury - ZHANG Yu-ting; TANG Xiao-yang; WU Gang (Linchuang shenzangbing zazhi)
With the improvement of the human living standard, fructose is more and more widely used as a food and beverage sweetener added to the new soft drinks and fruit juices. Fructose intake not only induces obesity, metabolic syndrome, but also increases the blood uric acid levels, inducing gout, which is the important factor for the incidence of chronic kidney disease and progression. More and more research progress has been made on the fructose-related metabolic mechanism and metabolic genes. How to control the excessive intake of fructose and prevent the adverse effects of fructose has attracted increasing attention.